Mediterranean Diet, Alzheimer Disease Biomarkers, and Brain Atrophy in Old Age. (15th June 2021) - Ballarini, Tommaso; Melo van Lent, Debora; Brunner, Julia; Schröder, Alina; Wolfsgruber, Steffen; Altenstein, Slawek; Brosseron, Frederic; Buerger, Katharina; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ertl-Wagner, Birgit; et al.
Abstract : Objective: To determine whether following a Mediterranean-like diet (MeDi) relates to cognitive functions and in vivo biomarkers for Alzheimer disease (AD), we analyzed cross-sectional data from the German DZNE-Longitudinal Cognitive Impairment and Dementia Study. Method: The sample (n = 512, mean age 69.5 ± 5.9 years) included 169 cognitively normal participants and individuals at higher AD risk (53 with relatives with AD, 209 with subjective cognitive decline, and 81 with mild cognitive impairment). We defined MeDi adherence according to the food frequency questionnaire. Brain volume outcomes were generated via voxel-based morphometry on T1-MRI, and cognitive performance was assessed with an extensive neuropsychological battery. AD-related biomarkers (β-amyloid42/40 [Aβ42/40 ] ratio, phosphorylated tau 181 [pTau181]) in CSF were assessed in n = 226 individuals. We analyzed the associations between MeDi and outcomes with linear regression models controlling for several covariates. In addition, we applied hypothesis-driven mediation and moderation analysis. Results: Higher MeDi adherence related to larger mediotemporal gray matter volume ( p < 0.05 family-wise error corrected), better memory (β ± SE = 0.03 ± 0.02; p = 0.038), and less amyloid (Aβ42/40 ratio, β ± SE = 0.003 ± 0.001; p = 0.008) and pTau181 (β ± SE = −1.96 ± 0.68; p = 0.004) pathology. Mediotemporal volume mediated the association between MeDi and memory (40% indirect mediation). Finally, MeDi favorably moderated the associations among Aβ42/40 ratio, pTau181, and mediotemporal atrophy. Results were consistent correcting for APOE -ε4 status. Conclusion: Our findings corroborate the view of MeDi as a protective factor against memory decline and mediotemporal atrophy. They suggest that these associations might be explained by a decrease of amyloidosis and tau pathology. Longitudinal and dietary intervention studies should further examine this conjecture and its treatment implications.